2020
DOI: 10.1109/access.2020.3029192
|View full text |Cite
|
Sign up to set email alerts
|

Unknown Radar Waveform Recognition Based on Transferred Deep Learning

Abstract: Radar signals are emerging constantly for urgent task because of its complex patterns and rich working modes. For some radar waveforms with known modulation methods, they can be identified by correlation between radar prior knowledge and the received signals by the reconnaissance receiver. As for the unknown radar signals, how to identify unknown radar waveforms under the condition of limited samples and low signal-to-noise ratio is a challenging problem. Aiming at the learning ability of the deep features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 23 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…However, QSAS is not simply a combination of different modulations and contains a lot of noise. Therefore, it is crucial to explore how to train the network and perform transfer learning (TL) [35,36] to adapt to different signal-to-noise ratios (SNR) [37,38] and improve noise adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…However, QSAS is not simply a combination of different modulations and contains a lot of noise. Therefore, it is crucial to explore how to train the network and perform transfer learning (TL) [35,36] to adapt to different signal-to-noise ratios (SNR) [37,38] and improve noise adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most popular FSL methods is transfer learning [22], which has been widely used in many fields, such as image classification [23] and text classification [24]. Some radar intra-pulse signal modulation classification algorithms based on transfer learning have also been proposed [25][26][27][28]. It has been found that the time-frequency image-based algorithms provide higher classification accuracy than the raw signal-based ones.…”
Section: Introductionmentioning
confidence: 99%
“…A deep learning framework for synthetic aperture radar automatic target recognition has been presented [23]- [25]. Moreover, a method combining CNNs and signal time-frequency transformation has been proposed to complete the classification and recognition of various radar signals, which acquire high accuracy under low signal-to-noise ratio [26]- [28].…”
Section: Introductionmentioning
confidence: 99%